Impact of dairy production technologies on productive and reproductive performance of dairy animals in Haryana - MEENA, B S; SANKHALA, GOPAL; MEENA, H R; MAJI, SAIKAT (The Indian Journal of Animal Sciences, 2017)
Management of productive and reproductive performance of livestock is vital to successful dairying, which is influenced by several parameters, viz. age at first calving, service period, calving interval, lactation length, lactation milk yield etc. These parameters are largely influenced by management in scientific manner from proper housing, feeding to preventive health measure is required to ensure proper health of the animal leaving the genetic traits.This study was conducted in adopted villages of NDRI and surrounding non-adopted villages in Karnal district of Haryana. Purpose was to analyse and compare the performance of animals in these villages and thus analyse the effect of long term project intervention by NDRI to introduce improved management practices among dairy farmers in this area. Data of 498 cattle and 488 buffalo were collected at monthly interval for two years starting from 2013 from 12 villages. Study revealed that except in case of lactation length of cross breed and buffalo, adopted villageshad outperformed non-adopted villages. But still in both adopted and non-adopted villages' performance need to be improved a lot to reach the desirable level of performance which should be somehow closer to the performance of these animals in model unit maintained by NDRI, Karnal.